Critical inclusion size prediction in refractory ceramics via finite element simulations. Issue 1 (January 2017) - Luchini, B.; Sciuti, V.F.; Angélico, R.A.; Canto, R.B.; Pandolfelli, V.C.
Abstract: Thermal expansion mismatch between matrix and aggregates can generate microcracks or decohesions when refractory ceramics are submitted to temperature variation. Earlier analytical studies have shown that these phenomena occur for inclusions with dimensions higher than a critical radius. These models are not reliable for inclusion amounts higher than 30 vol.%. In this paper, the critical inclusion size prediction by numerical simulation is presented resulting in more realistic models. The values obtained were compared to experimental ones from the literature with inclusion fractions of up to 45 vol.%. Finite element method results pointed out a change in the maximum thermomechanical stress location for volume fractions close to 43 vol.%. Up to this content, the maximum stress is at the matrix/inclusion interface, whereas for higher volume fractions, it is located in the midpoint between the inclusions. The advances attained by the present paper provide a suitable scientific foundation for designing flexible refractory compositions.